Spontaneous ovarian hyperstimulation syndrome: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication caused byexcessive response to controlled ovarian stimulation. It is characterized by ovarian enlargement andthe formation of multiple cysts. When OHSS occurs in spontaneous pregnancies it is known asspontaneous OHSS (sOHSS).Case presentation: A 31-year-old para 2+0 gravida 3 presented with gross abdominal distention at 11weeks of gestation. Abdominopelvic ultrasound revealed a single viable fetus at 12 weeks and 4days with large multicystic adnexal masses, which were suggestive of mucinous cystadenoma.Follow-up magnetic resonance imaging revealed ovarian hyperstimulation syndrome. Initial CA-125levels were >600 U/ml. Her symptoms were mild and resolved with conservative management. Sheeventually delivered preterm at 33 weeks.Conclusion: Pregnancy with sOHSS is a rare condition and may not be obvious. It may mimic otherovarian tumors, leading to premature termination of a normal pregnancy and unnecessary surgicalintervention.